MANAJEMEN SUMBER DAYA MANUSIA DALAM KEWIRAUSAHAAN - Erliyanti; Yurmaini (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2021)
Human resource management is defined as; planning, organising, mobilizing and supervising the procurement, development, compensation, integration, maintenance and termination of employment with a view to achieving the company's organizational goals in an integrated manner. This study is shown to determine the concept of human resources in entrepreneurship. The research method used is a qualitative method through a descriptive approach. Methods of data collection and research were carried out through various sources, namely literature review and related books. Based on the results of the analysis, it was found that HR Management in Entrepreneurship includes; Human Resource Management Concept; Rationalization of Human Resource Management; and Human Resource Management Process.